Dipyridamole Acts as Clinical Ferroptosis Inhibitor to Prevent from Tissue Injury - Xiao Zhuang; Shuang Shi; Shuo Liu; Yaqiong Jiao; Bin Huang; Yinghong Yang; Li Yang; Xinquan Yang; Hui Wang; Chunhui Liang; Dandan Song; Huaxiang Yu; et al. (Advanced Science)
Abstract Ferroptosis is a newly identified cell death triggered by iron‐induced lipid peroxidation. Numerous studies reveal that ferroptosis participates in multiple types of tissue injury including ischaemia–reperfusion (I/R) injury and doxorubicin (Dox)‐induced damage. Targeting ferroptosis is a promising approach for disease treatment as the blockade of ferroptosis efficiently alleviates the symptoms. However, no known ferroptosis inhibitors have been used for clinical treatment. Although certain clinical compounds act as ferroptosis inhibitors in vitro, whether these drugs cure tissue injury by suppressing ferroptosis is little known. Here, by screening a large panel of drugs used in the clinic, it is identified that dipyridamole significantly attenuates Dox or I/R‐induced cardiac injury. Moreover, dipyridamole can achieve a good therapeutic effect on  liver and kidney injury. Mechanistically, dipyridamole‐mediated ferroptosis inhibition is strictly dependent on solute carrier family 7 member 11 (SLC7A11). Dipyridamole down‐regulates the expression of ring finger protein 126 (RNF126), which is an E3 ligase to ubiquitinate SLC7A11 for proteasome degradation. Deficiency of SLC7A11 largely blocks the protective role of dipyridamole in vitro and in vivo. Together, the findings uncover that dipyridamole acts as a clinical compound to alleviate organ injury via suppressing ferroptosis, providing novel insights into the clinical therapy for ferroptosis‐related tissue damage.